2000
DOI: 10.1002/(sici)1096-9845(200004)29:4<481::aid-eqe918>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dynamic cable–deck interaction in a physical model of a cable‐stayed bridge. Part I: modal analysis

Abstract: SUMMARYA description of an experimental investigation involving the study of the dynamic interaction between the cables and the deck/towers system in cable-stayed bridges is presented. The work was carried out on a physical model of a cable-stayed bridge (the Jindo Bridge, in South Korea), whose characteristics of sti!ness and mass have been conveniently scaled. Standard modal analysis tests were performed using both an electrodynamic shaker and a shaking table, leading to the creation of a high-quality databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…A common practice in numerically modeling a cable is to use a single truss element with equivalent Young modulus. However, such definition implies the ignorance of the lateral cable vibration . In general, when the structure is under dead load only and the cable‐bridge interaction can be ignored, truss element can be safely used to model the cables.…”
Section: Numerical Simulation Of the Tied‐arch Bridgementioning
confidence: 99%
“…A common practice in numerically modeling a cable is to use a single truss element with equivalent Young modulus. However, such definition implies the ignorance of the lateral cable vibration . In general, when the structure is under dead load only and the cable‐bridge interaction can be ignored, truss element can be safely used to model the cables.…”
Section: Numerical Simulation Of the Tied‐arch Bridgementioning
confidence: 99%
“…The mass of each spine node is equally arranged at its anchorage points, so that the longitudinal rotational inertia of the deck can be considered in the model [25]. Several methods have been proposed to model the stay cables, such as the single truss model (one element cable system-OECS) [26] and multi-element cable system (MECS) [25,[27][28][29]. The OECS model does not account for the local cable transversal motion, and fails to describe its interaction with the global dynamics.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…It can be observed that these graphics exhibit not only the peaks that are associated with the global modes of the deck but also peaks that represent local modes of the stay cables or combined modes of the deck and stay cables (Caetano et al, 2000a(Caetano et al, , 2000b. This fact originates an increased difficulty in the identification of global modes whenever the corresponding natural frequency is close to a cable harmonic.…”
Section: Ambient Vibration Testsmentioning
confidence: 99%